Two new Schiff-base modified vanadium complexes with third-order NLO properties. Issue 17 (29th September 2020) - Zang, Ting-Ting; Cao, Jia-Peng; Du, Ze-Yu; Mei, Hua; Xu, Yan
Abstract: Two new Schiff-base modified vanadium complexes, [V IV O(C7 H5 O)2 (N2 C6 H10 )] (1 ) and [V V O2 (C7 H5 O)(N2 C6 H12 )] (2 ), were synthesized under hydrothermal conditions, in which salicylaldehyde and cyclohexanediamine were used directly to form Schiff-base ligands during the reactions. The structures of 1 and 2 were characterized by EA, FT-IR, UV-vis, SCXRD and PXRD, EPR spectroscopy and magnetic susceptibility measurement. Due to the good optical activity of Schiff-base ligands and the existence of conjugated benzene rings in 1 and 2, the delocalized electronic effects between Schiff-base ligands and vanadium can be improved. Therefore, the third-order non-linear optical (NLO) properties of these complexes were investigated. The results of the open aperture Z-scan tests show that the two-photon absorption (TPA) cross-sections ( σ ) of the complexes are 1033 and 1041GM, respectively, which indicated that they both have potential applications as NLO materials. Graphical Abstract: